Logistic service quality as factors on brand trust / Yong Azrina Ali Akbar...[et al.] - Ali Akbar, Yong Azrina; Wan Mahamad, Wan Shahrul Aziah; Roslan, Izzatul Husna; Shaik Alaudeen, Muharratul Sharifah; Setapa, Mariam (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Stiff competitions in the courier industry cause some of the industry players losing its customers. Customers keep switching around from one service provider to another for cheaper and better service. This trend greatly affected the industry players in the areas of market share, low sales and weak competitive positioning. It can be solved by practicing better logistic service quality in order to maintain brand trust. Eighty-eight respondents who are customers of a Singapore’s logistic company in Malaysia have been selected on the basis of convenience sampling to answer the questionnaire. The collected data was analyze by using SMART PLS. Finding shows that only three from four dimensions of logistic service quality which are timeliness, information quality and personnel contact quality influences brand trust. Meanwhile order accuracy does not affect brand trust. Thus, industry players in courier industry should focus on these elements to survive in the future.